A prospective trial of a novel low‐dose paclitaxel‐coated balloon therapy in patients with restenosis in drug‐eluting coronary stents Intracoronary Stenting and Angiographic Results: Optimizing Treatment of Drug Eluting Stent In‐stent REstenosis 3A (ISAR‐DESIRE 3A). Issue 3 (18th November 2021) - Kufner, Sebastian; Rai, Himanshu; Wiebe, Jens; Altevogt, Felix; Pyxaras, Stylianos; Joner, Michael; Xhepa, Erion; Cassese, Salvatore; Colleran, Roisin; Schunkert, Heribert; Zrenner, Bernhard; Kastrati, Adnan; et al.
Abstract: Objectives: We investigated the clinical efficacy of a paclitaxel‐coated balloon (PCB) with a novel matrix coating and reduced drug concentration in comparison with a widely used PCB with iopromide excipient. Methods: We prospectively enrolled patients with restenosis in drug‐eluting stents. All patients were treated with a novel low‐dose PCB with citrate‐based excipient (Agent PCB). Angiographic follow‐up was scheduled at 6–8 months. Outcomes were compared against those of patients treated with iopromide excipient PCB (SeQuent Please PCB) enrolled in a trial with identical inclusion and exclusion criteria. The primary endpoint was percent diameter stenosis (%DS) at follow‐up angiography. The primary hypothesis was that the investigational device would be non‐inferior to the control device (ClinicalTrials.gov Identifier: NCT02367495). Results: One hundred twenty‐five patients with 151 lesions were enrolled. Mean age was 68.1 ± 10.2 years, 40.8% had diabetes mellitus and 80.1% had focal morphology in‐stent restenosis. Follow‐up angiography data at 6–8 months was available for 102 (81.6%) patients. The Agent PCB was non‐inferior to the SeQuent Please PCB in terms of the primary endpoint (38.9 ± 17.5 vs. 38.1 ± 21.5%; p non‐inferiority  = 0.0056). Late lumen loss was also comparable between the groups (0.35 ± 0.55 vs. 0.37 ± 0.59; p  = 0.71). There was no difference between the groups in the incidence of TLR (27.7% vs. 22.1%; p  = 0.31), death or myocardial infarction (4.2% vs. 4.4%; p  = 0.92) or target lesion thrombosis (1.0% vs. 0.7%; p  = 0.93). Conclusion: In patients with DES restenosis, angioplasty with a novel PCB with citrate‐based excipient was non‐inferior to PCB with iopromide excipient in terms of angiographic outcome.